Chronotherapeutic Press-coated Tablets of Tramadol Hydrochloride: Formulation and In vitro Evaluation - Talakoti, Ramya Krishna (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The current investigation is aimed to develop and evaluate chronotherapeutic press-coated tablets (PCTs) of tramadol hydrochloride (TH) for rheumatoid arthritis. Materials and Methods: The core tablets were prepared with crospovidone and cross caramellose sodium as superdisintegrants. The PCTs containing TH in the inner core were prepared by compression coating with hydroxypropylmethyl cellulose (HPMC) E50 and HPMC E100 in varying ratios. The formulations were characterized for various pre- and post-compressional parameters. The effect of polymer properties and quantity of polymer on the lag time and drug release was investigated. Results and Discussion: The inner core tablet prepared with superdisintegrants showed desirable release pattern compiled with standard limits. The PCTs characterized for physicochemical properties and drug content are within the official limits. The swelling studies revealed that as a concentration of HPMC increased the swelling index was increased. The lag time values of PCTs (PCT1-PCT5) were found to be in the range of 2-7 h indicating that the lag time increased as the polymer concentration was increased. Optimized formulation PCT4 showed a predetermined lag time of 5 h with drug release of 98.74%. Fourier transform infra-red and differential scanning calorimetry study showed no evidence of interaction between the drug and polymers. The stability studies of selected PCT (PCT4) conducted at ambient temperature over 3 months showed similar dissolution profile with similarity factor f2 (61). Conclusion: The PCTs were successfully formulated with a combination of polymers HPMC E50 and HPMC E100 provided the better chronotherapeutic release characteristics.